The association between individual metabolic syndrome components, primary liver cancer and cirrhosis: A study in the Swedish AMORIS cohort. Issue 6 (21st June 2017) - Nderitu, Paul; Bosco, Cecilia; Garmo, Hans; Holmberg, Lars; Malmström, Håkan; Hammar, Niklas; Walldius, Göran; Jungner, Ingmar; Ross, Paul; Van Hemelrijck, Mieke
Abstract : Metabolic syndrome (MetS) is associated with non‐alcoholic fatty liver disease, which may progress to cirrhosis, a significant risk factor of hepatocellular carcinoma (HCC), the commonest malignant primary liver cancer (PLC). We investigated the association between the individual components of MetS (lipids, apolipoproteins, raised glucose, diabetes and obesity), PLC and cirrhosis. A total of 509, 436 participants from the Swedish AMORIS cohort, recruited between January 1985 and December 1996 (end‐date December 2011), aged ≥20 with baseline triglycerides (TG), total cholesterol (TC), glucose and liver enzymes were included. Those with baseline benign liver tumours, PLC or cirrhosis were excluded. Multivariate Cox regression, adjusted for age, gender, socio‐economic status, liver disease (excluding cirrhosis) and MetS factors were used to estimate the association with PLC and cirrhosis. There were 766 PLC and 2, 775 cirrhosis cases over 13 years. Raised TG, low TC, raised glucose, diabetes and low HDL were associated with an increased risk of developing PLC and cirrhosis. ApoB/ApoA‐I ratio were also associated with PLC, whilst low LDL, raised TG/HDL, low ApoA‐I and low ApoB were associated with cirrhosis. Obesity was significantly associated with PLC but not cirrhosis. Raised TG, low TC, raised glucose and diabetes showed stronger associations with PLC in participants with cirrhosis but many participants developed PLC without cirrhosis. Individual components of MetS (lipids, apolipoproteins, raised glucose, diabetes and obesity) were associated with an increased risk of developing PLC or cirrhosis. MetS components were more strongly associated with PLC with preceding cirrhosis history but many participants developed PLC without cirrhosis. Abstract : What's new? Given the rise in metabolic syndrome (MetS) and its association with non‐alcoholic fatty liver disease, which may progress to cirrhosis, itself a significant risk factor of hepatocellular carcinoma (HCC), the prevalence of primary liver cancer (PLC) may continue to rise. However, PLC association with individual MetS components or the role of cirrhosis remains unclear. Here, the authors found that lipids, apolipoproteins, glucose, diabetes and obesity were associated with an increased risk of developing PLC or cirrhosis and demonstrated the possible role of cirrhosis in PLC. The findings may inform strategies aimed at reducing the risk of developing cirrhosis or PLC.